PROGRAM UMAYA: UMKM MANDIRI DAN BERDAYA : Indonesia - Fikri, M. Andi (Journal of Social Comunity Services, 2024)
The problems experienced by PANCASONA the Small and Medium Business Enterprises (UMKM) are generally in the marketing and branding process. If we are examine further, the first one special problems in Pancasona UMKM there are limitations in product marketing due to a lack of understanding of digital marketing. profitable in promoting products effectively due to the lack of strong branding. Based on the problems were observed regarding the products in Pancasona UMKM. Then carry out an analysis of the potential of the small and Medium business enteeprises in Pancasona (UMKM) and determine a several activity programs it will be implemented on The Small and Medium Business enterprises PANCASONA UMKM , by carrying out companion and innovation programs for Pancasona UMKM to optimize the business potential of the, the small and medium program "PANCASONA" Independent and Empowered by The aim is empower the Small and Medium Business Enterprises (UMKM) in the region to be more independent and empowered. Some of the priority programs will be carried it out are creating banner designs, creating product knowledge and designing digital marketing via social media (Instagram).